39.3 RETINAL ANOMALIES IN SCHIZOPHRENIA AND THEIR CLINICAL SIGNIFICANCE. (9th April 2019) - Silverstein, Steven; Demmin, Docia; Erickson, Molly
Abstract: Background: Because the retina is part of the central nervous system, and develops from the same tissue as the brain, changes in retinal functioning often parallel changes in brain function. Alterations in retinal functioning in several neurological disorders, and in schizophrenia, have been observed using flash electroretinography (fERG). Methods: Flash ERG data, from both eyes and under both light- and dark-adapted conditions, were collected on 25 people with schizophrenia, 25 people with major depressive disorder (MDD), and 25 healthy controls in one study, and in separate groups of schizophrenia patients (ns >20 thus far) in two additional studies: one in which visual evoked potentials were recorded, and one in which cognitive functioning was assessed. Results: Schizophrenia patients demonstrated reduced amplitudes on waveforms reflecting photoreceptor, bipolar cell, and ganglion cell activity, across multiple tests. The MDD group data closely resembled the control group data, despite the severity of depression in this group (most subjects were inpatients). ERG amplitudes and latencies were unrelated to depression severity in both patient groups but were related to increased negative symptoms in the schizophrenia group. We will also report on relationships between ERG data and VEP data, and on relationships between ERG data and aspects of cognition in schizophrenia. Conclusions: Reduced signaling strength in the retina is a non-invasive indicator of CNS dysfunction in schizophrenia. Implications of relationships between ERG data and cortical response to visual stimuli, as well as cognition, will clarify the extent to which ERG data parallel, and can serve as a proxy for, aspects of brain function in the assessment of schizophrenia.